Concept of Rajyashma and its Treatment Approach in Ayurvedic Science -A Critical Analysis - Dhakar, Sanjay; Sharma, Surendra Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Rajayakshma refers to a group of disorders caused by the vitiation of the tridhatu and sapta dhatus.Ekadasha Rupa manifests as a result of indulging in Sahas veg sandarana, kshaya, and vishamashana. Rajayakshma is known as the "King of Diseases." As a result, it is known as Raja (King) and Yakshma (decay), which refers to massive fraying conditions. Parshwashool, Jwar, Kasa, and Raktashthiwana are Rajayakshma symptoms. In today’s world, Rajayakshma is associated with tuberculosis. There is a differentiation between Rajayakshmaand Pulmonary Tuberculosis in terms of pathophysiology.Both have a very similar clinical presentation. Due to environmental changes, changes in behavior, diet habits, low quality of life, population boom, undernutrition, and a lack of understanding about the causes of disease and modern lifestyle, it is a major public health problem in India.The present review highlights the Ayurvedic aspect of Rajyasmaand its treatment through Ayurveda.